207k views
2 votes
Solve the system of equations please:
y=(x^2)+3x-6
y=x+2

1 Answer

1 vote

Answer:

(- 4, - 2 ) and (2, 4 )

Explanation:

Given the 2 equations

y = x² + 3x - 6 → (1)

y = x + 2 → (2)

Substitute y = x² + 3x - 6 into (2)

x² + 3x - 6 = x + 2 ( subtract x + 2 from both sides )

x² + 2x - 8 = 0 ← in standard form

(x + 4)(x - 2) = 0 ← in factored form

Equate each factor to zero and solve for x

x + 4 = 0 ⇒ x = - 4

x - 2 = 0 ⇒ x = 2

Substitute these values into (2) for corresponding values of y

x = - 4 → y = - 4 + 2 = - 2 ⇒ (- 4, - 2 )

x = 2 → y = 2 + 2 = 4 ⇒ (2, 4 )

User Mitch McMabers
by
4.4k points